Induced Pluripotent Stem Cells Are Sensitive to DNA Damage - Zhang, Minjie (Genomics Proteomics Bioinformatics, 2013)
Induced pluripotent stem cells (iPSCs) resemble embryonic stem cells (ESCs) in morphology, gene expression and in vitro differentiation, raising new hope for personalized clinical therapy. While many efforts have been made to improve reprogramming efficiency, significant problems such as genomic instability of iPSCs need to be addressed before clinical therapy. In this study, we try to figure out the real genomic state of iPSCs and their DNA damage response to ionizing radiation (IR). We found that iPSC line 3FB4-1 had lower DNA damage repair ability than mouse embryonic fibroblast (MEF) cells, from which 3FB4-1line was derived. After the introduction of DNA damage by IR, the number of γ-H2AX foci in 3FB4-1 increased modestly compared to a large increase seen in MEF, albeit both significantly (P < 0.01). In addition, whole-genome sequencing analysis showed that after IR, 3FB4-1 possessed more point mutations than MEF and the point mutations spread all over chromosomes. These observations provide evidence that iPSCs are more sensitive to ionizing radiation and their relatively low DNA damage repair capacity may account for their high radiosensitivity. The compromised DNA damage repair capacity of iPSCs should be considered when used in clinical therapy.